2022
DOI: 10.1111/2041-210x.13995
|View full text |Cite
|
Sign up to set email alerts
|

Detection of standing retention trees in boreal forests with airborne laser scanning point clouds and multispectral imagery

Abstract: 1. In a landscape consisting primarily of intensive forestry interspersed with some protected areas, multifunctional forestry with retention trees can play a crucial role in nature conservation. Accurate mapping of retention trees is important for guiding landscape-level conservation and forest management and improving landscape connectivity. Sizeable dead and living retention trees play a particularly important ecological role but even their large-scale inventory is often intensive through field work and/or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Studies have demonstrated that the LiDAR measurement error for individual tree heights (of a given species) could be less than 1.0 m (Holmgren and Persson, 2004). Retention trees can be detected on clear-cut areas (Holmström et al, 2019, Hardenbol et al, 2022, Lindbladh et al, 2022 via visual cues. However, visual interpretation of orthophotos is a subjective way to find trees, and trees retained in clear-cut areas may not be present at thinning.…”
Section: Biodiversity Management In Thinningmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that the LiDAR measurement error for individual tree heights (of a given species) could be less than 1.0 m (Holmgren and Persson, 2004). Retention trees can be detected on clear-cut areas (Holmström et al, 2019, Hardenbol et al, 2022, Lindbladh et al, 2022 via visual cues. However, visual interpretation of orthophotos is a subjective way to find trees, and trees retained in clear-cut areas may not be present at thinning.…”
Section: Biodiversity Management In Thinningmentioning
confidence: 99%
“…This advancement may thus provide an unparallel data source that can be used for biodiversity conservation. Many studies have successfully located and characterised retention trees using point clouds from ALS (Naesset and Økland, 2002, Holmgren and Persson, 2004, Hardenbol et al, 2022. However, the use of the canopy height model is sparser (Mustonen et al, 2008, Zielewska-Büttner et al, 2016 and not necessarily targeted for biodiversity conservation management.…”
Section: Mapping Of Retention (Paper Iv)mentioning
confidence: 99%
“…Parallel to testing such fundamental ecological hypotheses, efforts have also been moving towards directly deriving required metrics from active data sources, which can potentially be further applied as inputs for a wide range of studies in ecology and conservation. In this Special Feature, Hardenbol et al (2022) discuss how combining airborne active LiDAR and passive multispectral data can help in detecting retention trees, an important component for safeguarding biodiversity of fauna and flora in close‐to‐nature forestry (e.g. Fedrowitz et al, 2014).…”
Section: Thematic Groups Being Covered In the Sfmentioning
confidence: 99%
“…This can be of practical value in, for example, Nordic Europe, with country‐wide aerial data regularly acquired by forest services. Hardenbol et al (2022) achieved detection rates ranging from 41.7% (dead trees) to 83.8% (living trees) by applying an individual tree detection algorithm, although higher omission errors occurred for dead trees with smaller diameters and heights. However, adding spectral metrics from colour infrared photography did not systematically enhance the overall accuracies of classifying living conifers, living broadleaves or dead trees, indicating that the sole use of LiDAR metrics may suffice for separating retention trees from other trees.…”
Section: Thematic Groups Being Covered In the Sfmentioning
confidence: 99%
See 1 more Smart Citation